THE IMPLEMENTATION OF THE RIGHT TO EDUCATION FOR JUVENILE INMATES AT THE CLASS II SPECIAL CHILD DEVELOPMENT INSTITUTION IN MAROS - Muhammad Zulfadli; Suci Puspitasari; Andi Dewi Riang (Humano: Jurnal Penelitian, 2025)
This research aims to find out: 1). How to implement the educational rights of prisoners and children at LPKA Class II Maros. 2). Understand the efforts made to implement educational rights for child prisoners at LPKA Class II Maros. 3). Knowing the obstacles in implementing educational rights for prisoners at LPKA Class II Maros. Descriptive qualitative research is the methodology employed. Three methods of gathering data are employed: documentation, interviews, and observation. Examining research-related data, conducting in-depth interviews, reducing data, presenting data, and drawing conclusions are all steps in the data gathering process that researchers do. Since not every child prisoner at the Class II Maros Special Development Institution for Children has been granted the right to education, the research's findings indicate that the implementation of educational rights for juvenile offenders at LPKA Class II Maros has not gone as planned. The small percentage of youngsters who do not satisfy the necessary documentation requirements is the impediment. By attempting to expand data collecting and communication about education, attempts are being made to satisfy the educational rights of juvenile offenders.